Generative AI for Aviation Maintenance: Optimizing Predictive Analytics through Strategic Prompt Engineering and Hybrid Human AI Collaboration - SeyyedAbdolHojjat MoghadasNian (The 10th international Conference on Knowledge and Technology of Mechanical, Electrical Engineering and Computer Of Iran, 2025)
This study examines the effect of strategic prompt engineering on the diagnostic accuracy of generative AI for predictive maintenance in aviation and evaluates the performance of hybrid human AI maintenance teams. Using a mixed methods approach combining quantitative analysis of diagnostic accuracy and mean time to repair (MTTR) metrics with qualitative interviews of industry experts, results show a >11% improvement in fault prediction accuracy and a significant reduction in MTTR. Findings contribute a KPI driven framework and propose governance guidelines for ethical AI deployment in aviation.